Hoffmann's Syndrome: A Rare Complication of Hypothyroidism - Paz-Ibarra, José Luis (2025)
Up to 80% of patients with hypothyroidism present with neuromuscular symptoms. We report the case of a 56-year-old male with a two-year history of symptoms suggestive of hypothyroidism, which worsened over the last five months, with difficulty walking, muscle rigidity, and cramps. Laboratory tests confirmed primary hypothyroidism with elevated creatine kinase (CK) and lactate dehydrogenase (LDH) levels. Following treatment with levothyroxine, the clinical and biochemical response was favorable. Hoffmann syndrome, an atypical form of hypothyroid myopathy, is rare and primarily affects males with long-standing hypothyroidism. It is characterized by pseudohypertrophy and progressive muscle weakness, affecting less than 10% of hypothyroid patients. The pathogenesis is thought to involve alterations in the IGF1–PI3K–Akt/mTOR and myostatin-Smad3 pathways. Treatment with levothyroxine normalizes hormonal and CK levels within weeks; however, muscle recovery may be slower, varying with the severity of the condition.